English Learning and Innovation Skills in 21st: Implementation of Critical Thinking, Creativity, Communication, and Collaboration - Novia, Fitri; Desti Nurdianti; M Bambang Purwanto (Asian Journal of Applied Education (AJAE), 2024)
This essay looks at how to improve English language learning through the application of critical thinking, creativity, communication, and teamwork abilities. Students are expected to be able to navigate life's obstacles on their own thanks to the skills they have acquired since, among other things, a generation raised in the 21st century that is inundated with "conveniences" that have two sides can have both beneficial and harmful effects. Training students in social skills and global awareness is the main reason for the need of utilizing critical thinking, creativity, communication, and collaboration learning abilities in education. These skills include problem-solving, communication, creativity and innovation, and cooperation. To provide students with the full range of talents and abilities necessary for a more affluent life, all of these competencies must be developed during the learning process